2008
DOI: 10.1001/archpedi.162.6.557
|View full text |Cite
|
Sign up to set email alerts
|

Association Between 100% Juice Consumption and Nutrient Intake and Weight of Children Aged 2 to 11 Years

Abstract: On average, children consumed less than the maximum amounts of 100% juice recommended by the American Academy of Pediatrics. One hundred percent juice consumption was associated with better nutrient intake than in the nonconsumption group and was not associated with weight status or the likelihood of being overweight in children 2 to 11 years of age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
84
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(95 citation statements)
references
References 48 publications
9
84
2
Order By: Relevance
“…Since consumption of 100% juice was associated with increased potassium intake, 24 it is possible that exclusion of 100% juice from the CV+CF category may have underestimated the potassium intake among CV+CF consumers and overestimated the potassium intake among non-consumers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since consumption of 100% juice was associated with increased potassium intake, 24 it is possible that exclusion of 100% juice from the CV+CF category may have underestimated the potassium intake among CV+CF consumers and overestimated the potassium intake among non-consumers.…”
Section: Discussionmentioning
confidence: 99%
“…Noting that most Americans fail to meet DGA recommendations for vegetables and fruits, [9][10][11][12] the Academy encourages food and nutrition practitioners to recommend, along with fresh forms, inclusion of frozen, canned, and dried forms of vegetables and fruits, which have similar nutrient profiles, [13][14][15] but may offer consumers additional benefits with respect to cost, seasonality, storage, and transport. 8,13 Studies have examined associations of whole vegetables and fruits, [16][17][18] individual vegetables and fruits, [19][20][21][22] dried fruits, 23 and 100% fruit juices [24][25] with nutritional or health outcomes. Little is known about the overall effect that consumption of canned vegetables and fruit (CV+CF) has on nutrient intake, dietary quality, and health measures.…”
Section: Introductionmentioning
confidence: 99%
“…56 A more recent study suggested that varying intakes of 100% juice were not associated with obesity. 57 More research is required to better define this relationship. 3.…”
Section: Infantsmentioning
confidence: 99%
“…Although some studies have shown an association between 100 % FJ consumption and weight (4)(5)(6)(7) , the majority have not (8)(9)(10)(11)(12)(13)(14) . A systematic review published in 2008 showed no consistent association between consumption of 100 % FJ and overweight/obesity in children or adolescents (14) .…”
mentioning
confidence: 99%